14 Dynamic changes of oedema and late gadolinium enhancement after acute myocardial infarction and their relationship to functional recovery and salvage index. (9th June 2011) - Dall'Armellina, E; Karia, N; Lindsay, A; Karamitsos, T D; Ferreira, V; Robson, M D; Kellman, P; Francis, J M; Forfar, C; Prendergast, B; Banning, A P; Channon, K; et al.
Abstract : Introduction: Changes in myocardial tissue in acute ischaemia are dynamic and complex and the characteristics of myocardial tissue on cardiovascular magnetic resonance (CMR) in the acute setting are not fully defined. We investigated changes in oedema and late gadolinium enhancement (LGE) with serial imaging early after acute MI, relating these to global and segmental myocardial function at 6 months. Methods and Results: CMR scans were performed on 30 patients with ST elevation MI (STEMI) treated by primary PCI at each of 4 time points: 12–48 h (TP1); 5–7 days (TP2); 14–17 days (TP3); and 6 months (TP4). All patients showed oedema at TP1. The mean volume of oedema (% LV) was 37±16 at TP1 and 39±17 at TP2 with a reduction to 24±13 (p<0.01) by TP 3. Myocardial segments with oedema also had increased signal on LGE at TP1 (κ=0.77; p<0.001). At TP1, the proportion of segments with wall motion impairment increased in relation to the extent of both myocardial oedema (p<0.01) and LGE (p<0.01). The volume of LGE decreased significantly between TP1 and TP4 (27±15% vs 22±12%; p=0.002). Of segments showing LGE at 48 h, 50% showed resolution by 6 months. In segments with such a reduction in LGE, 65% also showed improved wall motion (p<0.0001). The area of LGE measured at 6 months correlated more strongly with 48-h troponin (R2=0.84; p<0.01) than at TP1 (R2=0.5). The difference in LGE between TP1 and TP4 had profound effects on the calculation of salvage index (26±21% at TP1 vs 42±23% at TP4; p<0.02). Conclusions: (1) Myocardial oedema was unchanged over the first week but decreased by 15 days; (2) a large majority of segments that were positive for oedema also showed LGE, assessed at 12–48 h; (3) In 46% of patients, LGE present on early scans had diminished in size by 6 months, (4) resolution of LGE was associated with improvement in function; (5) the reduction in LGE at the later time had a profound effect on the calculation of salvage index, which varied by up to ∼60%, depending on the time point used. (6) From a clinical perspective, the use of acute LGE may severely underestimate salvaged myocardium and should not be used to predict recovery of myocardial function.